Peran Komunikasi Guru TK Antasari Banjarbaru dalam Membangun Karakter Anak Didiknya - Putri, Widiya Salsabella; Novianti, Lieta Dwi; Hapsari, Adelia Winda (LPPM Institut Pendidikan Nusantara Global, 2025)
This study was motivated by the desire to find out how teacher interactions shape the personalities of their students. This study uses a descriptive research strategy based on qualitative data. Informants who are kindergarten teachers in Antasari Banjarbaru were contacted through interviews and written documents. Data analysis was carried out using qualitative data analysis techniques, which provide a comprehensive picture of the research findings by referring to the current theoretical framework. The results of the study show that the role of teacher communication in shaping the characteristics of students faces obstacles in understanding the character of early childhood students, especially for children who have tantrums and special needs, requiring a high level of patience and good coordination with parents.